It’s time to take action: Turning an anti-corruption culture into a way of life - FIRMANSYAH, MUHAMMAD REYHAN (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that hinders social, economic, and political development in Indonesia, and has spread to the student environment. This study aims to analyze the importance of building an anti-corruption culture as a lifestyle among the younger generation. The method used in this study is a literature study (library research) by reviewing various relevant scientific sources related to anti-corruption education and Pancasila values. The results show that corrupt behavior is influenced by internal, environmental, and structural factors, such as weak internalization of integrity values, academic pressure, and an unsupportive system. The discussion emphasizes that character education based on Pancasila values ​​plays a crucial role in instilling honesty, responsibility, and integrity. The implementation of an anti-corruption culture can be done through academic and non-academic activities, including student organizations and the use of digital media. In conclusion, students have a strategic role as agents of change in building a sustainable anti-corruption culture through the application of integrity values ​​in everyday life.